Local Election in 2017 in Indonesia: Test of Tendencies to Abuse Grant Expenditure and Social Aid Expenditure Budget by Incumbent Candidates - Abdul Hafiz Tanjung (Journal of Accounting and Investment, 2020)
Research aims: This research was conducted and aimed to examine the tendencies to abuse the power of incumbent candidates in making budget of grant expenditure and social aid expenditure to support their political interests in the local election on February 15th, 2017, in Indonesia.Design/Methodology/Approach: There were two populations in this study, namely the first population of district/municipality areas that carried out the elections, which included incumbent candidates in size of 53 districts/municipalities, and the population of both district/municipal regions that carried out the elections, which had no incumbent candidates in size of 41 districts/municipalities. Samples were chosen by cluster random sampling with proportional allocation between districts and municipals. The sample for the first population was 35 districts/municipalities, consisting of 26 districts and nine municipalities, while the sample for the second population was 29 districts/municipalities, consisting of 25 districts and four municipalities. Two statistical analyses were employed in this research; parametric statistics, i.e., paired t-test, independent t-test variances unknown but equal, and the non-parametric statistics, i.e., Mann-Whitney U test and Wilcoxon test. Data normality test using w/s test had been done to determine which analysis to be used.Research findings: The result of this research showed that there was empirical evidence of tendencies to abuse incumbent candidates’ power in making budget of grant expenditure and social aid expenditure to support their political interests in the local election on February 15th, 2017.Theoretical contribution/Originality: This study’s results reinforce that the incumbent regional head has more authority in budget management, especially during local government head of elections.Practitioner/Policy implication:  Based on the findings, the central government needs to change the rules on the use of grant expenditure and social aid expenditure on local governments from indirect expenditure to direct expenditure that can be measured by performance.Research limitation/Implication: This study has a limitation that lies in grant expenditure, and social aid expenditure studied, which only looked at the increase or decrease in the number of realization of grant expenditure and social aid expenditure in the local government budget realization report, not on the effectiveness of its distribution.